Preparation methods of nitrogen-doped graded double-shell hollow carbon microspheres and noble metal-loaded catalyst of nitrogen-doped graded double-shell hollow carbon microspheres

By preparing nitrogen-doped graded bicantilized hollow carbon microspheres in water/alcohol/ammonia water system, the problem of difficulty in preparing nitrogen-doped hollow mesoporous carbon microspheres without surfactants is solved, high yield and low pollution of carbon material preparation is achieved, and electrochemical performance is improved.

CN119524747APending Publication Date: 2025-02-28SHAXIAN HONGSHENG PLASTIC CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311082459.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to prepare nitrogen-doped hollow mesoporous carbon microspheres without surfactants, resulting in low yields of carbon materials and severe environmental pollution.

Method used

In the water/alcohol/ammonia water system, a low molecular weight soluble resin is formed by condensation reaction of resorcinol, amines and formaldehyde, and silica is formed as the core after adding tetraethyl silicate. Then, a bihulled structure of the polymer resin is formed, and finally a nitrogen-doped bihulled hollow carbon microsphere is obtained by carbonizing and removing silica.

Benefits of technology

The preparation of nitrogen-doped bihulled hollow carbon microspheres without surfactants has been achieved, which improves the yield of carbon materials, reduces environmental pollution, and improves the electrochemical performance of carbon microspheres.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524747A_ABST
    Figure CN119524747A_ABST
Patent Text Reader

Abstract

The invention relates to the field of carbon material preparation, in particular to a nitrogen-doped graded double-shell hollow carbon microsphere and a preparation method of a noble metal-loaded catalyst of the nitrogen-doped graded double-shell hollow carbon microsphere. The preparation method comprises the following steps: adding resorcinol and amines into a water / alcohol / ammonia water system, then adding formaldehyde to carry out condensation reaction, and when the reaction time is 30-99% of the time required for turbid appearance, adding tetraethyl silicate and continuously reacting to form a polymer resin / silicon dioxide first composite shell layer; and raising the temperature, continuing the reaction to form a second polymer resin shell layer, and sequentially centrifuging, washing, drying, carbonizing and removing silicon dioxide to obtain the nitrogen-doped graded double-shell hollow carbon microspheres. According to the nitrogen-doped graded double-shell hollow carbon microsphere, the inner shell mainly comprises mesopores, the outer shell mainly comprises micropores, the main components of the inner shell are carbon and a very small amount of nitrogen, the main component of the outer shell is nitrogen-doped carbon, the adsorption of ions on the surface of the carbon microsphere can be promoted, and the electrochemical performance of the carbon microsphere serving as a catalytic material and an electrode material is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of carbon material preparation, and in particular to a method for preparing nitrogen-doped graded double-shell hollow carbon microspheres and a noble metal-loaded catalyst thereof. Background Art

[0002] The development of renewable energy has become an important way for humans to solve environmental pollution and resource shortages. However, most renewable energy sources lack stability due to intermittent generation, which is not conducive to power transmission. Therefore, it is necessary to develop stable energy storage and conversion devices. Energy storage and conversion devices are mostly electrode materials, and carbon materials are an important component of electrode materials in existing energy storage devices.

[0003] Phenolic resin is an ideal polymer precursor for preparing carbon microspheres, but ordinary phenolic resins are obtained after carbonization. Microporous structure, while electrode carbon materials require hollow mesoporous structure. At present, the methods for preparing hollow mesoporous carbon microspheres include template method, dissolution method, etc. For example, Fang (Langmuir, 2008, 24 (12068-72)) et al. prepared exothermic hollow mesoporous carbon microspheres with mesopore size of 3.1nm using mesoporous silica as template. Dai et al. (Nano Lett, 2013, 13 (1): 207-12) used silica and hexadecyltrimethylammonium chloride as templates and structure regulators to obtain mesoporous carbon microspheres with pore size of 2.4-4.7nm and large mesopore size. Mesoporous carbon microspheres can also improve the material capacitance performance by introducing nitrogen elements. Nitrogen atoms have similar electron cloud density to carbon atoms and can be easily introduced into the carbon skeleton. Chen (Journal of The Electrochemical Society, 2017, 164 (9): A1918-A23) et al. used hexadecyltrimethylammonium bromide as a surfactant and silicon dioxide as a hollow template to prepare nitrogen-doped hollow mesoporous carbon microspheres. The above preparation methods all require the assistance of surfactants, which are expensive. Surfactants are directly converted into carbon dioxide during carbonization, which not only reduces the yield of carbon materials, but also increases environmental pollution. The preparation method of nitrogen-doped hollow mesoporous carbon microspheres based on surfactant-free is a huge challenge. Summary of the invention

[0004] The technical problem to be solved by the present invention is: a method for preparing nitrogen-doped graded double-shell hollow carbon microspheres and a noble metal-loaded catalyst thereof without using a surfactant.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing nitrogen-doped graded double-shell hollow carbon microspheres, comprising the following steps:

[0006] S1: adding resorcinol and amines to a water / alcohol / ammonia system and stirring uniformly to obtain a solution;

[0007] S2: adding formaldehyde to the solution to carry out condensation reaction at 10-40°C, and when the reaction takes 30-99% of the time required for turbidity to appear, adding tetraethyl silicate;

[0008] S3: Continue the reaction to form the first composite shell of polymer resin / silicon dioxide and obtain SiO 2 @NPF / SiO 2 Microspheres;

[0009] S4: After the temperature is raised to 80-200°C, the reaction is continued to form a second shell layer of polymer resin, and SiO 2 @NPF / SiO 2 @NPF Microspheres;

[0010] S5: SiO 2 @NPF / SiO 2 @NPF microspheres are carbonized and silicon dioxide is removed to obtain nitrogen-doped graded double-shell hollow carbon microspheres.

[0011] Another technical solution adopted by the present invention is: the nitrogen-doped graded double-shell hollow carbon microspheres prepared by the preparation method of the above-mentioned nitrogen-doped graded double-shell hollow carbon microspheres have an outer shell layer with a microporous structure and an inner shell layer with a mesoporous structure.

[0012] Another technical solution adopted by the present invention is: a method for preparing a precious metal-loaded catalyst, which is prepared by using the above-mentioned nitrogen-doped graded double-shell hollow carbon microspheres. The specific preparation method is: dispersing the nitrogen-doped graded double-shell hollow carbon microspheres in a solvent, adding a precious metal compound, stirring to allow the precious metal compound to be dispersed and adsorbed on the nitrogen-doped graded double-shell hollow carbon microspheres, then distilling off the solvent, and obtaining the precious metal-loaded catalyst after high-temperature carbonization.

[0013] The beneficial effects of the present invention are as follows: the preparation method of phenolic resin-based nitrogen-doped graded double-shell hollow carbon microspheres provided by the present invention comprises the following steps: in the absence of a surfactant, in a water / alcohol / ammonia system, firstly condensing part of resorcinol, a small part of amines and formaldehyde to form a low molecular weight soluble resin; when the reaction lasts for 30 to 99% of the time required for turbidity to appear, adding tetraethyl silicate, and hydrolyzing and condensing the tetraethyl silicate to produce silicon dioxide as the core; thereafter, when the resorcinol, amines and formaldehyde are condensed to produce insoluble polymer resin particles, the polymer resin particles and the silicon dioxide produced by the hydrolysis and condensation of tetraethyl silicate are coated on the surface of the silicon dioxide core to form SiO 2 @NPF / SiO 2(Silica coated polymer resin / silica) microspheres; then the temperature is raised to 80-200°C, and the remaining small amount of resorcinol, the remaining majority of amines and formaldehyde condense to produce a polymer resin coated on the outermost layer to form SiO 2 @NPF / SiO 2 @NPF (silica coated polymer resin / silica coated polymer resin) microspheres; finally, after carbonization and removal of silica, phenolic resin-based nitrogen-doped hierarchical double-shell hollow carbon microspheres are obtained.

[0014] The phenolic resin-based nitrogen-doped hierarchical double-shell hollow carbon microspheres have a double-shell hierarchical pore structure, the inner shell is mainly mesoporous, the outer shell is mainly microporous, the inner shell is mainly composed of carbon and a very small amount of nitrogen, and the outer shell is mainly composed of nitrogen-doped carbon. The high-concentration nitrogen-doped microporous structure of the outer shell can give the carbon microspheres good surface wetting and unique electronic benefits, promote the adsorption of ions on the surface of the carbon microspheres, effectively improve the electrochemical properties of the carbon microspheres as catalytic materials and electrode materials, and show good supercapacitor performance. No surfactant is used in the preparation process, which can increase the yield of carbon materials and reduce environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a TEM test image of the carbon microspheres prepared in Example 1 of the present invention;

[0016] Figure 2 This is a TEM test image of the carbon microspheres prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0017] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in combination with the implementation modes and the accompanying drawings.

[0018] A method for preparing nitrogen-doped hierarchical double-shell hollow carbon microspheres comprises the following steps:

[0019] S1: adding resorcinol and amines to a water / alcohol / ammonia system and stirring uniformly to obtain a solution;

[0020] S2: adding formaldehyde to the solution to carry out condensation reaction at 10-40°C, and when the reaction takes 30-99% of the time required for turbidity to appear, adding tetraethyl silicate;

[0021] S3: Continue the reaction to form the first composite shell of polymer resin / silicon dioxide and obtain SiO 2 @NPF / SiO 2 Microspheres;

[0022] S4: After the temperature is raised to 80-200° C., the reaction is continued to form a second shell layer of the polymer resin, and microspheres are obtained after centrifugation, washing and drying in sequence;

[0023] S5: SiO 2 @NPF / SiO 2 @NPF microspheres are carbonized and silicon dioxide is removed to obtain nitrogen-doped graded double-shell hollow carbon microspheres.

[0024] Preferably, tetraethyl silicate is added when the reaction reaches 40-60% of the time required for turbidity to appear.

[0025] From the above description, it can be seen that the beneficial effects of the present invention are: the nitrogen-doped hierarchical double-shell hollow carbon microspheres prepared by the present invention have a hierarchical pore structure combining mesopores and a large number of micropores, the inner shell is mainly mesopores, and the outer shell is mainly micropores, which have both the selectivity of mesopores and the specific surface area of ​​micropores. The microporous structure is conducive to increasing the specific surface area, improving the enrichment of ions, improving electrochemical properties and adsorption, etc.; the mesopores of the inner shell can reduce the transmission resistance of ions and further improve the various properties of carbon microspheres; the innermost hollow structure can be used as a storage space for ions to improve electrochemical properties. There are differences in the elemental composition of the inner and outer shells. The main components of the inner shell are carbon and a very small amount of nitrogen, and the main component of the outer shell is nitrogen-doped carbon with hierarchical characteristics. The carbon microspheres have effective nitrogen doping, and the high-concentration nitrogen-doped microporous structure of the outer shell can give the carbon microspheres good surface wetting and unique electronic benefits, promote the adsorption of ions on the surface of the carbon microspheres, effectively improve the electrochemical properties of the carbon microspheres as catalytic materials and electrode materials, and show good supercapacitor performance. No surfactant is used in the preparation process, which can increase the yield of carbon materials and reduce environmental pollution.

[0026] The specific preparation principle of the present invention is as follows:

[0027] Step 1: Under the catalytic action of a water / alcohol system and ammonia water, part of resorcinol, a small amount of amines and formaldehyde are preferentially reacted to a certain extent to form a soluble nitrogen-containing phenolic resin with a certain molecular weight.

[0028] Step 2: Then tetraethyl silicate is added. Under the catalysis of water / alcohol system and ammonia water, tetraethyl silicate is first rapidly hydrolyzed and condensed to form silica and become the core. In the process of hydrolysis and condensation of tetraethyl silicate to form silica, the condensation reaction of resorcinol, amines and formaldehyde is also continuing. When the reaction reaches a certain extent, the molecular weight of phenolic resin reaches a large enough level and particles are precipitated. At this time, phenolic resin particles and silica particles are coated on the surface of the silica core together to form the first composite shell of phenolic resin / silicon dioxide. Low temperature is adopted in step 1 and step 2 to promote the preferred reaction of resorcinol and ethyl orthosilicate.

[0029] Step 3: The reaction temperature is then raised. The increase in temperature promotes further condensation of the amines, so that the remaining large amount of amines and a small amount of resorcinol continue to condense with formaldehyde to form nitrogen-doped phenolic resin, which is coated outside the first composite shell layer, and finally forms SiO 2 @NPF / SiO 2 @NPF (silica coated polymer resin / silica coated polymer resin) microspheres.

[0030] In the preparation process, by controlling the addition time of tetraethyl silicate, the preparation of carbon microspheres with differences in elemental composition and pore structure of the inner and outer shells is achieved. Since the hydrolysis and condensation of tetraethyl silicate is delayed, when resorcinol, a small amount of amines and formaldehyde react to precipitate microparticles, there is still a certain amount of tetraethyl silicate and its soluble condensation product in the system, and the silicon dioxide produced by its hydrolysis and condensation will be assembled together with the phenolic resin microparticles. Therefore, the preferential condensation of resorcinol, a small amount of amines and formaldehyde significantly increases the concentration of tetraethyl silicate and its soluble condensation product in the later system, so that more silicon dioxide will be co-coated with phenolic resin, increasing the amount of silicon dioxide in the first composite shell layer, which is conducive to the formation of more and larger mesopores. Since the reaction rate of resorcinol is significantly higher than that of amines, in the early reaction, it is mainly resorcinol and formaldehyde that are condensed and reactive, and the phenolic resin formed and silicon dioxide are co-coated to form the first composite shell layer of phenolic resin / silicon dioxide. When the reaction temperature is raised, a large amount of amines and a small amount of unreacted resorcinol continue to react with formaldehyde to form a condensation reaction, and the formed phenolic resin with a high nitrogen content is coated on the outside of the first composite shell to form a second shell. Since the core of the final microsphere formed is silicon dioxide, the first shell is a phenolic resin / silicon dioxide composite shell, and the second shell is a phenolic resin with a high nitrogen content, silicon-carbon microspheres are obtained after carbonization, the core is silicon dioxide, the first shell is a carbon / silicon dioxide composite shell, and the second shell is nitrogen-doped carbon. After removing the silicon dioxide in the core and the silicon dioxide in the first shell, hollow carbon microspheres are obtained, the first shell is mesoporous, the second shell is microporous, the first shell contains a small amount of nitrogen, and the second shell contains a large amount of nitrogen.

[0031] The silica produced by the early hydrolysis and condensation of tetraethyl silicate serves as a hollow template, while the silica produced by the later hydrolysis and condensation becomes a pore-forming agent for the first shell layer. After removing the silica, the first shell layer with mesopores is obtained.

[0032] Further, the alcohol in the water / alcohol / ammonia system is at least one of methanol, ethanol, propanol, butanol, octanol, pentanol, hexanol, heptanol, hemp alcohol, ethylene glycol, glycerol, propylene glycol, and pentaerythritol. Preferably, the alcohol in the water / alcohol / ammonia system is ethanol.

[0033] Further, the volume ratio of water to alcohol in the water / alcohol / ammonia system is 1:1 to 1:10. Preferably, the volume ratio of water to alcohol in the water / alcohol / ammonia system is 1:5 to 1:10.

[0034] Furthermore, the amine is any one of OAT, melamine and urea.

[0035] Among them, OAT is a residue produced in the melamine production process.

[0036] From the above description, we can see that OAT is currently mainly treated as solid waste, with high treatment costs. Its main components are melamine, cyanuric acid, ammeline, ammeline, etc. It has similar reaction characteristics to melamine and can react with formaldehyde at an appropriate temperature to form nitrogen-doped phenolic resin. Using OAT to prepare carbon microspheres is conducive to achieving green and low-carbon production.

[0037] Further, the concentration of resorcinol in the solution is 1-100 mg / mL, and the mass of the amine is 10%-100% of the mass of resorcinol. Preferably, the concentration of resorcinol in the solution is 1-20 mg / mL, and the mass of the amine is 40%-60% of the mass of resorcinol.

[0038] From the above description, it can be seen that the size of the microspheres can be adjusted by adjusting the concentration of resorcinol. As the concentration of resorcinol increases, the size of the microspheres becomes larger, especially the thickness of the first composite shell layer increases. The amount of amines used affects the nitrogen content in the microspheres and the size of the microspheres. The more amines are used, the higher the nitrogen content, the larger the size of the microspheres, and especially the thickness of the second shell layer increases.

[0039] Further, the molar ratio of ammonia water to resorcinol is 1:1 to 20:1. Preferably, the molar ratio of ammonia water to resorcinol is 10:1 to 15:1.

[0040] From the above description, it can be seen that ammonia water as a catalyst can promote the reaction of tetraethyl silicate, amines and resorcinol, and ammonium ions can also promote the co-coating of phenolic resin and silica on the surface of silica to ensure the smooth progress of the reaction. At the same time, it also affects the size of the microspheres. The increase in the content of ammonia water leads to faster reaction and smaller size of the microspheres.

[0041] Further, the molar ratio of tetraethyl silicate to resorcinol is 1:2 to 20:1. Preferably, the molar ratio of tetraethyl silicate to resorcinol is 1:1 to 10:1.

[0042] From the above description, it can be seen that the silicon dioxide produced by the hydrolysis and condensation of tetraethyl orthosilicate in the early stage is used as the core to form the hollow structure of the carbon microspheres, and the silicon dioxide produced in the later stage is co-coated with the phenolic resin to form the mesoporous structure of the carbon microspheres, which improves the electrochemical performance of the carbon microspheres. The high content of tetraethyl silicate can expand the cavity of the hollow carbon microspheres and improve the capacitance.

[0043] Furthermore, the formaldehyde is paraformaldehyde or a formaldehyde aqueous solution.

[0044] Further, the molar ratio of formaldehyde to resorcinol is 3:2 to 10:1. Preferably, the molar ratio of formaldehyde to resorcinol is 3:2 to 5:1.

[0045] From the above description, it can be seen that a proper excess of formaldehyde is beneficial to the cross-linking of phenolic resin.

[0046] Please refer to Figure 1 Another technical solution adopted by the present invention is: the nitrogen-doped graded double-shell hollow carbon microspheres prepared by the above-mentioned preparation method of nitrogen-doped graded double-shell hollow carbon microspheres, the outer shell of the nitrogen-doped graded double-shell hollow carbon microspheres has a microporous structure, and the inner shell has a mesoporous structure.

[0047] From the above description, it can be seen that the inner and outer shells of the nitrogen-doped graded double-shell hollow carbon microspheres of the present invention differ in pore structure and elemental composition. The first shell formed at a lower temperature is mainly composed of a composite shell of phenolic resin and silica, and mesopores can be obtained after carbonization and removal of silica; the second shell is formed by further condensation of amines at a higher temperature, and its main component is a nitrogen-containing phenolic resin. After carbonization, a nitrogen-doped microporous shell is obtained. The high-concentration nitrogen-doped microporous structure of the outer shell can give the carbon microspheres good surface wetting and unique electronic benefits, promote the adsorption of ions on the surface of the carbon microspheres, and effectively improve the electrochemical properties of the carbon microspheres as catalytic materials and electrode materials.

[0048] Another technical solution adopted by the present invention is: a method for preparing a precious metal-loaded catalyst, which is prepared by using the above-mentioned nitrogen-doped graded double-shell hollow carbon microspheres. The specific preparation method is: dispersing the nitrogen-doped graded double-shell hollow carbon microspheres in a solvent, adding a precious metal compound, stirring to allow the precious metal compound to be dispersed and adsorbed on the nitrogen-doped graded double-shell hollow carbon microspheres, then distilling off the solvent, and obtaining the precious metal-loaded catalyst after high-temperature carbonization.

[0049] Furthermore, the precious metal compound is at least one of rhodium trichloride, gold trichloride, gold(II) chloride, palladium chloride, chloroauric acid, chloroplatinic acid, potassium hexachloroplatinate, sodium hexachloroplatinate, platinum tetrachloride, platinum acetylacetonate, palladium nitrate, palladium acetate, and tetrachloropalladium ammonium.

[0050] Embodiment 1 of the present invention is: a method for preparing nitrogen-doped graded double-shell hollow carbon microspheres, comprising the following steps:

[0051] S1: Add 25% by mass ammonia water into water / ethanol, mix and stir evenly; the volume ratio of water to ethanol is 1:7;

[0052] S2: add resorcinol and melamine, stir evenly to obtain a solution; the concentration of resorcinol in the solution is 5 mg / mL; the mass of melamine is 50% of the mass of resorcinol; the molar ratio of ammonia water to resorcinol is 11:1;

[0053] S3: adding a 37% by mass formaldehyde aqueous solution to the solution, raising the temperature to 25° C., so that the formaldehyde, resorcinol and a small amount of melamine begin to undergo a condensation reaction to form a low molecular weight soluble resin; the molar ratio of formaldehyde to resorcinol in the formaldehyde aqueous solution is 3:1;

[0054] S4: When the reaction time reaches 40% of the time required for turbidity to appear, tetraethyl silicate is added; the molar ratio of tetraethyl silicate to resorcinol is 3.4:1;

[0055] S5: After the reaction continues, the first composite shell of polymer resin / silicon dioxide is formed, and SiO 2 @NPF / SiO 2 (Silica coated polymer resin / silica) microspheres;

[0056] S6: After the temperature is raised to 100°C, the reaction is continued to form a second shell layer of polymer resin, and SiO is obtained after centrifugation, washing and drying. 2 @NPF / SiO 2 @NPF (silica coated polymer resin / silica coated polymer resin) microspheres;

[0057] S7: The microspheres are carbonized and the silica is removed to obtain phenolic resin-based nitrogen-doped hierarchical double-shell hollow carbon microspheres DNHMCS1.

[0058] The prepared nitrogen-doped hierarchical double-shell hollow carbon microspheres were tested. The pore size of the carbon microspheres was about 14 nm, and the BET specific surface area and pore volume were 586 m 2 g -1 and 1.7cm 3 g -1 , XPS (X-ray photoelectron spectroscopy) tested the nitrogen content to be 5.6%. Figure 1 is the TEM image of the carbon microspheres. Figure 1 It can be seen that the carbon microspheres are hollow structures with thicker wall layers, loose inner shell layers and dense outer shell layers.

[0059] Preparation of platinum-loaded carbon microspheres: 1.25 g of nitrogen-doped graded double-shell hollow carbon microspheres were dispersed in 120 mL of ethanol solution, followed by the addition of 0.05 g of chloroplatinic acid. After stirring, the mixture was dispersed and adsorbed using ultrasonic treatment, the solvent was distilled off, and then carbonized at 700 °C for 3 h under a nitrogen atmosphere to obtain a platinum-loaded carbon microsphere catalyst.

[0060] Comparative Example 1 of the present invention is: a method for preparing hollow microporous carbon microspheres, comprising the following steps:

[0061] S1: Add resorcinol to water / ethanol, add 25% by mass of ammonia water, and stir evenly; the volume ratio of water to ethanol is 1:7; the concentration of resorcinol in the solution is 5 mg / ml; the molar ratio of ammonia water to resorcinol is 11:1;

[0062] S2: adding 37% formaldehyde aqueous solution and tetraethyl silicate to obtain a turbid liquid after reaction; the molar ratio of formaldehyde to resorcinol is 2:1; the molar ratio of tetraethyl silicate to resorcinol is 3.4:1;

[0063] S3: centrifuging, washing and drying the turbid liquid to obtain silica-coated phenolic resin microspheres;

[0064] S4: Carbonizing the microspheres and removing silicon dioxide to obtain hollow microporous carbon microspheres HC.

[0065] The prepared hollow microporous carbon microspheres were tested. The pore size of the carbon microspheres was less than 2nm, and the BET specific surface area and pore volume were 514m 2 g -1 and 1.23cm 3 g -1 . Figure 2 This is the TEM image of the carbon microspheres.

[0066] Preparation of platinum-loaded carbon microspheres: 1.25 g of nitrogen-doped graded double-shell hollow carbon microspheres were dispersed in 120 mL of ethanol solution, followed by the addition of 0.05 g of chloroplatinic acid. After stirring, the mixture was dispersed and adsorbed using ultrasonic treatment, the solvent was distilled off, and then carbonized at 700 °C for 3 h under a nitrogen atmosphere to obtain a platinum-loaded carbon microsphere catalyst.

[0067] Embodiment 2 of the present invention is: a method for preparing nitrogen-doped graded double-shell hollow carbon microspheres, comprising the following steps:

[0068] S1: Add 25% by mass ammonia water into water / ethanol, mix and stir evenly; the volume ratio of water to ethanol is 1:7;

[0069] S2: add resorcinol and OTA, stir evenly to obtain a solution; the concentration of resorcinol in the solution is 5 mg / mL; the mass of OTA is 50% of the mass of resorcinol; the molar ratio of ammonia water to resorcinol is 11:1;

[0070] S3: adding a 37% by mass formaldehyde aqueous solution to the solution, raising the temperature to 25° C., so that formaldehyde, resorcinol and a small amount of OTA begin to undergo a condensation reaction to form a low molecular weight soluble resin; the molar ratio of formaldehyde to resorcinol in the formaldehyde aqueous solution is 3:1;

[0071] S4: When the reaction time reaches 40% of the time required for turbidity to appear, tetraethyl silicate is added; the molar ratio of tetraethyl silicate to resorcinol is 3.4:1;

[0072] S5: After the reaction continues, the first composite shell of polymer resin / silicon dioxide is formed, and SiO 2 @NPF / SiO 2 (Silica coated polymer resin / silica) microspheres;

[0073] S6: After the temperature is raised to 100°C, the reaction is continued to form a second shell layer of polymer resin, and SiO is obtained after centrifugation, washing and drying. 2 @NPF / SiO 2 @NPF (silica coated polymer resin / silica coated polymer resin) microspheres;

[0074] S7: The microspheres are carbonized and the silica is removed to obtain phenolic resin-based nitrogen-doped hierarchical double-shell hollow carbon microspheres DNHMCS2.

[0075] The prepared nitrogen-doped hierarchical double-shell hollow carbon microspheres were tested. The pore size of the carbon microspheres was about 14 nm, and the BET specific surface area and pore volume were 586.2 m 2 g -1 and 2.0cm 3 g -1 , XPS (X-ray photoelectron spectroscopy) tested the nitrogen content to be 4.5%.

[0076] Preparation of gold-loaded carbon microspheres: 1.2 g of carbon microspheres were dispersed in 120 mL of ethanol solution, followed by the addition of 0.08 g of chloroauric acid, stirring and then ultrasonic treatment was used to disperse and adsorb the carbon microspheres, the solvent was distilled off, and then carbonization was performed at 700 °C for 3 h under a nitrogen atmosphere to obtain a platinum-loaded carbon microsphere catalyst.

[0077] Embodiment 3 of the present invention is: a method for preparing nitrogen-doped graded double-shell hollow carbon microspheres, comprising the following steps:

[0078] S1: Add 25% by mass ammonia water into water / ethanol, mix and stir evenly; the volume ratio of water to ethanol is 1:7;

[0079] S2: add resorcinol and melamine, stir evenly to obtain a solution; the concentration of resorcinol in the solution is 5 mg / mL; the mass of melamine is 50% of the mass of resorcinol; the molar ratio of ammonia water to resorcinol is 11:1;

[0080] S3: Adding a 37% by mass formaldehyde aqueous solution into the solution, raising the temperature to 25°C, so that formaldehyde, resorcinol and a small amount of melamine begin to undergo condensation reaction to form a low molecular weight soluble resin; the molar ratio of formaldehyde to resorcinol in the formaldehyde aqueous solution is 3:1.

[0081] S4: When the reaction time reaches 60% of the time required for turbidity to appear, tetraethyl silicate is added; the molar ratio of tetraethyl silicate to resorcinol is 3.4:1.

[0082] S5: After the reaction continues, the first composite shell of polymer resin / silicon dioxide is formed, and SiO 2 @NPF / SiO 2 (Silica coated polymer resin / silica) microspheres;

[0083] S6: After the temperature is raised to 100°C, the reaction is continued to form a second shell layer of polymer resin, and SiO is obtained after centrifugation, washing and drying. 2 @NPF / SiO 2 @NPF (silica coated polymer resin / silica coated polymer resin) microspheres;

[0084] S7: The microspheres are carbonized and the silica is removed to obtain phenolic resin-based nitrogen-doped hierarchical double-shell hollow carbon microspheres DNHMCS3.

[0085] The prepared nitrogen-doped hierarchical double-shell hollow carbon microspheres were tested. The pore size of the carbon microspheres was about 13 nm, and the BET specific surface area and pore volume were 615.5 m 2 g -1 and 2.2cm 3 g -1 , XPS (X-ray photoelectron spectroscopy) tested the nitrogen content to be 5.2%.

[0086] Preparation of rhodium-loaded carbon microspheres: 1.2 g of carbon microspheres were dispersed in 120 mL of ethanol solution, followed by the addition of 4 mL of rhodium trichloride aqueous solution (concentration of 0.015 g / mL), stirred and then ultrasonically treated to disperse and adsorb, the solvent was distilled off, and then carbonized at 700 °C for 3 h under a nitrogen atmosphere to obtain a rhodium-loaded carbon microsphere catalyst.

[0087] Embodiment 4 of the present invention is: a method for preparing nitrogen-doped graded double-shell hollow carbon microspheres, comprising the following steps:

[0088] S1: Add 25% by mass ammonia water to water / methanol / propanol / butanol / octanol / pentanol, and mix and stir evenly; the volume ratio of water / methanol / propanol / butanol is 1:2:2:2:2:2;

[0089] S2: add resorcinol and urea, stir evenly to obtain a solution; the concentration of resorcinol in the solution is 1 mg / mL; the mass of urea is 10% of the mass of resorcinol; the molar ratio of ammonia water to resorcinol is 1:1;

[0090] S3: adding a 37% by mass formaldehyde aqueous solution to the solution, raising the temperature to 10° C., so that formaldehyde, resorcinol and a small amount of urea begin to undergo a condensation reaction to form a low molecular weight soluble resin; the molar ratio of formaldehyde to resorcinol in the formaldehyde aqueous solution is 3:2;

[0091] S4: When the reaction takes 99% of the time required for turbidity to appear, tetraethyl silicate is added; the molar ratio of tetraethyl silicate to resorcinol is 1:2;

[0092] S5: After the reaction continues, the first composite shell of polymer resin / silicon dioxide is formed, and SiO 2 @NPF / SiO 2 (Silica coated polymer resin / silica) microspheres;

[0093] S6: After the temperature is raised to 200°C, the reaction is continued to form a second shell layer of polymer resin, and SiO is obtained after centrifugation, washing and drying. 2 @NPF / SiO 2 @NPF (silica coated polymer resin / silica coated polymer resin) microspheres;

[0094] S7: Carbonizing the microspheres and removing silicon dioxide to obtain phenolic resin-based nitrogen-doped hierarchical double-shell hollow carbon microspheres.

[0095] Embodiment 5 of the present invention is: a method for preparing nitrogen-doped graded double-shell hollow carbon microspheres, comprising the following steps:

[0096] S1: Add 25% by mass ammonia water into water / ethylene glycol, mix and stir evenly; the volume ratio of water to ethylene glycol is 1:1;

[0097] S2: adding resorcinol and melamine, stirring evenly to obtain a solution; the concentration of resorcinol in the solution is 100 mg / mL; the mass of melamine is 100% of the mass of resorcinol; the molar ratio of ammonia water to resorcinol is 20:1;

[0098] S3: adding a 37% by mass formaldehyde aqueous solution to the solution, raising the temperature to 40° C., so that the formaldehyde, resorcinol and a small amount of melamine begin to undergo a condensation reaction to form a low molecular weight soluble resin; the molar ratio of formaldehyde to resorcinol in the formaldehyde aqueous solution is 10:1;

[0099] S4: When the reaction time reaches 30% of the time required for turbidity to appear, tetraethyl silicate is added; the molar ratio of tetraethyl silicate to resorcinol is 20:1;

[0100] S5: After the reaction continues, the first composite shell of polymer resin / silicon dioxide is formed, and SiO 2 @NPF / SiO 2 (Silica coated polymer resin / silica) microspheres;

[0101] S6: After the temperature is raised to 80°C, the reaction is continued to form a second shell layer of polymer resin, and SiO is obtained after centrifugation, washing and drying. 2 @NPF / SiO 2 @NPF (silica coated polymer resin / silica coated polymer resin) microspheres;

[0102] S7: After carbonizing the microspheres and removing silica, phenolic resin-based nitrogen-doped hierarchical double-shell hollow carbon microspheres DNHMCS1 are obtained.

[0103] The electrochemical performance of the supported carbon microsphere catalysts prepared in Examples 1 to 3 and Comparative Example 1 was tested respectively. The test method was as follows: 0.004 g of the supported carbon microsphere catalyst was added with 0.2 mL of isopropanol, 0.77 mL of water and 0.032 mL of a 5 wt.% Nafion (perfluorosulfonic acid polymer) solution, and a uniform slurry was obtained after ultrasonic dispersion. 10 μL of the slurry was added dropwise to 0.196 cm 2 The surface of the glassy carbon electrode was dried in a fume hood for 2 h to obtain a loading of 0.2 mg / cm 2 The working electrode was used to pass oxygen at a flow rate of 50 ml / min for 30 minutes to saturate the solution with oxygen. The test was carried out using 6M KOH (potassium hydroxide) electrolyte and a three-electrode system, which included a reference electrode (Hg / HgO), a counter electrode (Pt sheet) and a working electrode.

[0104] The supercapacitor performance test was performed on the carbon microspheres prepared in Examples 1 to 3 and Comparative Example 1 respectively, and the test method was as follows:

[0105] Step 1: Evenly mix the prepared carbon microspheres with the binder PVDF and carbon black in a mass ratio of 8:1:1, and apply the mixture on an electrode sheet to obtain a working electrode.

[0106] Step 2: On a CHI760E electrochemical workstation, a constant current charge-discharge test was performed using a 6 M KOH electrolyte and a three-electrode system. The electrodes of the three-electrode system included a reference electrode (Hg / HgO), a counter electrode (Pt sheet), and a working electrode.

[0107] The test results of catalytic performance and supercapacitor performance are shown in Table 1.

[0108] Table 1

[0109]

[0110]

[0111] As can be seen from Table 1, the catalysts prepared in Examples 1 to 3 have higher half-wave potential and limiting current density than those in Comparative Example 1, and have better catalytic performance; the electrodes prepared in Examples 1 to 3 have better capacitance and capacity retention than those in Comparative Example 1. Therefore, the supported catalysts and electrodes prepared using the nitrogen-doped hierarchical double-shell hollow carbon microspheres obtained in the present invention as materials have good electrochemical properties.

[0112] In summary, the present invention provides nitrogen-doped hierarchical double-shell hollow carbon microspheres having a hierarchical pore structure combining mesopores and a large number of micropores, wherein the inner shell is mainly mesopores and the outer shell is mainly micropores, and has both the selectivity of mesopores and the specific surface area of ​​micropores. The inner and outer shells differ in elemental composition, wherein the main components of the inner shell are carbon and a very small amount of nitrogen, and the main component of the outer shell is nitrogen-doped carbon with hierarchical characteristics. The carbon microspheres have effective nitrogen doping, and the high-concentration nitrogen-doped microporous structure of the outer shell can give the carbon microspheres good surface wetting and unique electronic benefits, promote the adsorption of ions on the surface of the carbon microspheres, effectively improve the electrochemical properties of the carbon microspheres as catalytic materials and electrode materials, and show good supercapacitor performance.

[0113] In the water / alcohol / ammonia system, the hydrolysis and condensation rate of tetraethyl silicate is significantly greater than the condensation rate of resorcinol-formaldehyde, and the condensation rate of resorcinol-formaldehyde is significantly greater than the condensation rate of the amines and formaldehyde. Therefore, if tetraethyl silicate and amines, resorcinol and formaldehyde are added to the water / alcohol / ammonia system together, tetraethyl silicate will be rapidly hydrolyzed and condensed to form silica microspheres. When the amines, resorcinol and formaldehyde are condensed to a degree sufficient to precipitate phenolic resin particles, the tetraethyl silicate in the system has basically reacted to form silica microspheres. The phenolic resin particles can only be coated on the surface of silica alone to form silica-coated phenolic resin microspheres. After carbonization and removal of the silica in the inner core, only hollow microporous carbon microspheres can be obtained.

[0114] Therefore, in the absence of a surfactant, the preparation method of the present invention preferentially condenses a small amount of amines and resorcinol with formaldehyde in water / alcohol under the catalytic action of ammonia water. When the reaction takes 30 to 99% of the time required for turbidity to appear, the small amount of amines and resorcinol have been condensed with formaldehyde to a certain extent. At this time, tetraethyl silicate is added, which can just make the small amount of amines and resorcinol condense with formaldehyde until particles are precipitated. There is still enough tetraethyl silicate and its soluble condensation product in the system. The silicon dioxide produced by the hydrolysis of tetraethyl silicate and its soluble condensation product will be co-coated with the phenolic resin particles to form a first composite shell layer of phenolic resin / silicon dioxide. After carbonizing and removing the silicon dioxide in the shell layer, a first shell layer with mesopores will be obtained. The timing of adding tetraethyl silicate is very critical. If it is added too early, the hydrolysis and condensation of tetraethyl silicate will be more thorough, and there will not be enough silica in the later system to achieve co-assembly, making it difficult to form a composite shell layer and the subsequent mesoporous layer. If it is added more late, resorcinol and formaldehyde will undergo a deeper condensation to form phenolic resin particles, and the formed phenolic resin particles will become the core, and a hollow structure cannot be obtained.

[0115] Increasing the reaction temperature is the key to obtaining the second shell layer. Since the reaction activity of the amines is very low, in the early stage, it is mainly resorcinol that reacts with formaldehyde. After increasing the reaction temperature, a large amount of amines will react with formaldehyde to form a nitrogen-containing phenolic resin coated on the first shell layer to form a second shell layer. The second shell layer obtained after carbonization and etching is a nitrogen-doped microporous structure.

[0116] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention's specification and drawings, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing nitrogen-doped hierarchical double-shell hollow carbon microspheres, characterized in that: The following steps are involved: S1: adding resorcinol and amines to a water / alcohol / ammonia system and stirring uniformly to obtain a solution; S2: adding formaldehyde to the solution to carry out condensation reaction at 10-40°C, and when the reaction takes 30-99% of the time required for turbidity to appear, adding tetraethyl silicate; S3: Continue the reaction to form the first composite shell of polymer resin / silicon dioxide and obtain SiO2@NPF / SiO2 microspheres; S4: After the temperature is raised to 80-200°C, the reaction is continued to form a second shell layer of polymer resin, and SiO2@NPF / SiO2@NPF microspheres are obtained after centrifugation, washing and drying in sequence; S5: Carbonizing SiO2@NPF / SiO2@NPF microspheres and removing silicon dioxide to obtain nitrogen-doped graded double-shell hollow carbon microspheres.

2. The method for preparing nitrogen-doped hierarchical double-shell hollow carbon microspheres according to claim 1, characterized in that: The alcohol in the water / alcohol / ammonia system is at least one of methanol, ethanol, propanol, butanol, octanol, pentanol, hexanol, heptanol, hemptanol, ethylene glycol, glycerol, propylene glycol, and pentaerythritol.

3. The method for preparing nitrogen-doped hierarchical double-shell hollow carbon microspheres according to claim 1, characterized in that: The volume ratio of water to alcohol in the water / alcohol / ammonia water system is 1:1 to 1:

10.

4. The method for preparing nitrogen-doped hierarchical double-shell hollow carbon microspheres according to claim 1, characterized in that: The amine is any one of OAT, melamine and urea.

5. The method for preparing nitrogen-doped hierarchical double-shell hollow carbon microspheres according to claim 1, characterized in that: The concentration of the resorcinol in the solution is 1-100 mg / mL, and the mass of the amines is 10%-100% of the mass of the resorcinol.

6. The method for preparing nitrogen-doped hierarchical double-shell hollow carbon microspheres according to claim 1, characterized in that: The molar ratio of the ammonia water to resorcinol is 1:1 to 20:

1.

7. The method for preparing nitrogen-doped hierarchical double-shell hollow carbon microspheres according to claim 1, characterized in that: The molar ratio of tetraethyl silicate to resorcinol is 1:2 to 20:

1.

8. The method for preparing nitrogen-doped hierarchical double-shell hollow carbon microspheres according to claim 1, characterized in that: The molar ratio of formaldehyde to resorcinol is 3:2 to 10:

1.

9. The nitrogen-doped graded double-shell hollow carbon microspheres prepared by the method for preparing nitrogen-doped graded double-shell hollow carbon microspheres according to any one of claims 1 to 8, wherein the outer shell of the nitrogen-doped graded double-shell hollow carbon microspheres has a microporous structure, and the inner shell has a mesoporous structure.

10. A method for preparing a noble metal supported catalyst, characterized in that: The catalyst is prepared by using the nitrogen-doped graded double-shell hollow carbon microspheres as described in claim 9. The specific preparation method is: dispersing the nitrogen-doped graded double-shell hollow carbon microspheres in a solvent, adding a precious metal compound, stirring to disperse and adsorb the precious metal compound on the nitrogen-doped graded double-shell hollow carbon microspheres, then distilling off the solvent, and obtaining a precious metal-loaded catalyst after high-temperature carbonization.